UJI DAYA HAMBAT Aspergillus niger PADA BERBAGAI BAHAN PEMBAWA TERHADAP Phytopththora palmivora PENYEBAB BUSUK BUAH KAKAO (Theobroma cacao L.) - Wahdania, Indah; Asrul, Asrul; Rosmini, Rosmini (AGROTEKBIS, 2017)
Cocoa pod disease (BBK) caused by the fungus Phytophthora palmivora is one of the prime diseases that can affect cocoa production systems in the world . This disease can cause yield losses of up to 90 % , especially in the rainy season and the dry season. The objective of the research is to determine theinhibitor abilityof fungus A. niger in various carriesr and storage time durationonPhytophtora palmivora causing rotten disease of cocoa. This is an experimental research designed by using Random Complete Design withÂ factorial patern, that were carries and storage period with 3 replication, factor 1: (P0 = control), (P1 = white glutinous rice flour + cassava starch), (P2 = cassava starch). (P3 = white glutinous rice flour + sweet corn flour), (P4 = white glutinous rice flour), (P5 = ripe coconut flour). Factor 2: (A1 = 1 week storage period), (A2 = 2 weeks storage period), (A3 = 3 weeks storage period), (A4 = 4 weeks storage period). Result of the research showed that the carrier of white glutinous rice flour + sweet corn flour (P3) and ripe coconut flour (P5) and in A3 storage period (3 weeks) is more effective to inhibiting P.palmivora growth, therefore can be used as a carrier to support A.niger fungus growth.Â Key words: Aspergillusniger, Cacao, and Carrier